A Study on Dividend Determinants for Korea's Information Technology Firms - Sungsin Kim,; Ji-Yong Seo, (Asian Academy of Management Journal of Accounting and Finance, 2014)
In this study, we analyse the determinants of dividend policies of information technology (IT) firms listed on the Korean stock market and use a logit regression model to examine Korean IT firms' propensity to pay dividends based on the life-cycle hypothesis. The analysis yields several findings: first, the firms pay relatively small dividends in the growth stage, which increase over time as their businesses mature. Second, profitability shows a positive correlation with propensity to pay dividends. Third, firms that paid out more dividends in the past continue to pay relatively more dividends. Meanwhile, dividend policies do not show a significant correlation with firm size or growth opportunities. In addition, dividend policies have no relation to the catering incentive (investor fads for dividends) or risk. These observations suggest that Korean IT firms' propensity to pay dividends is supported by the life-cycle hypothesis and that the declining dividends from the mid-2000s can be attributed to deteriorating profits.